Existence of the classical solution to the multi -dimensional Stefan problem on a finite interval of time - Borodin , M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The existence of classical solutions of the two-phase Stefan problem on any finite interval is shown.